2015
DOI: 10.1097/aud.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude Modulation Detection and Speech Recognition in Late-Implanted Prelingually and Postlingually Deafened Cochlear Implant Users

Abstract: Prelingually deafened CI users were less sensitive to temporal modulations than postlingually deafened CI users, and the attenuation rate of their TMTF was steeper. For all CI users, subjects with better amplitude modulation detection skills tended to score better on measures of speech understanding. Significant correlations with low modulation frequencies were found only for the prelingually deafened CI users and not for the postlingually deafened CI users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The temporal envelope is even more important for CI users because the CI cannot extract adequate spectral information due to a limited number of frequency channels (Shannon et al, 1995;Fu, 2002), whereas low frequency temporal information is relatively well delivered through the CI. Since behavioral studies have shown that the ability to detect temporal variations has a strong correlation with speech perception (Won et al, 2011;De Ruiter et al, 2015), there has been an effort to measure how the brain processes temporal variations using auditory-evoked responses such as the ASSR and the mismatch negativity response. Using EASSRs to AM pulse trains of 4 and 40 Hz, Luke et al (2015) found that the EASSR amplitudes at 40 Hz were related to the AM detection thresholds in five CI users and suggested the clinical significance of EASSR as an objective measure of site-specific temporal sensitivity for CIs.…”
Section: Am Change As a Paradigm To Assess Cortical Temporal Processimentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal envelope is even more important for CI users because the CI cannot extract adequate spectral information due to a limited number of frequency channels (Shannon et al, 1995;Fu, 2002), whereas low frequency temporal information is relatively well delivered through the CI. Since behavioral studies have shown that the ability to detect temporal variations has a strong correlation with speech perception (Won et al, 2011;De Ruiter et al, 2015), there has been an effort to measure how the brain processes temporal variations using auditory-evoked responses such as the ASSR and the mismatch negativity response. Using EASSRs to AM pulse trains of 4 and 40 Hz, Luke et al (2015) found that the EASSR amplitudes at 40 Hz were related to the AM detection thresholds in five CI users and suggested the clinical significance of EASSR as an objective measure of site-specific temporal sensitivity for CIs.…”
Section: Am Change As a Paradigm To Assess Cortical Temporal Processimentioning
confidence: 99%
“…Compared with normal-hearing (NH) individuals, the TMTF of CI users has a higher overall AM threshold that is more pronounced at higher frequencies resulting in a lower frequency TMTF filter cutoff and subsequently this property is associated with reduced speech perception ability (Won et al, 2011). The ability to detect high-frequency AM (50-300 Hz) is correlated to speech perception in CI users including tone (Luo et al, 2008), consonants (Cazals et al, 1994), and word recognition (Won et al, 2011) and phonemes (De Ruiter et al, 2015). Recently, low frequency AM rate discrimination at 4 Hz shortly after CI activation time was shown to be a predictor of speech perception at 6 months post-activation (Erb et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that CI listeners can make considerable use of AMs to assist with speech recognition (Shannon et al, 1995), as evidenced by some remarkable early studies that showed implant recipients could obtain a degree of speech understanding with only a single channel device (Tyler, 1988;Rosen et al, 1989;Rosen, 1992). This demonstrates that a large proportion of the information necessary for successful speech recognition is associated with the modulating envelope of speech signals (De Ruiter et al, 2015;Dimitrijevic et al, 2016;Han and Dimitrijevic, 2020). Therefore, it is plausible that poor speech performance amongst CI users could result from inadequate transmission of the AM signal from the CI to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…If the child chooses a wrong pictured word that has the correct stress pattern, it still scores a point in stress perception. While the MTS is a commonly used tool for the evaluation of speech perception and employed also nowadays with adult CI users (e.g., De Ruiter et al, 2015 ), one problem of the test is that it confounds stress pattern perception with the number of syllables in the case of the monosyllables. Another problem is that it can be only performed with children old enough to understand the task and point at the correct picture and who have already acquired a certain set of vocabulary.…”
Section: Introductionmentioning
confidence: 99%